Evaluation of Interleukin-10 (G-1082A) Promoter Polymorphism in Preeclampsia - Sabnavis, Sowmya; Ramaiah, Aruna; Sunitha, Tella; Nallari, Pratibha; Jyothy, Akka; Venkateshwari, Ananthapur (Journal of Reproduction & Infertility, 2013)
Background: Preeclampsia is a pregnancy-specific syndrome that may be life-threatening, especially to the fetus. Several causes have been reported that may have a possible role in the development of the disorder. Interleukin-10 affect maternal intravascular inflammation, as well as endothelial dysfunction. The aim of this study was to investigate the association between IL-10 G-1082A polymorphism and pre-eclampsia. Methods: A total of eighty-eight pregnant women with preeclampsia and 100 women with normal pregnancy attending the Gynecological unit of Government Maternity Hospital, Petlaburz, Hyderabad, India, were considered for the study. A standard amplification refractory mutation system (ARMS) PCR was carried out for genotyping IL-10 G-1082A promoter polymorphism in all the participants. Genotypic distribution of the control and patient groups were compared with values predicted by Hardy-Weinberg equilibrium using χ2 test. Odd ratios (OR) and their respective 95% confidence intervals were used to measure the strength of association between IL-10 gene polymorphism and preeclampsia. Results: The frequencies of IL-10 G-1082A genotypes, GG, GA and AA, were 17.8%, 41.09% and 41.09% in women with preeclampsia and 25%, 28% and 47% in the controls respectively. There was no significant difference in the distribution of genotypes and alleles of IL-10 G-1082A between the two groups (Test power=0.66). Conclusion: The present study suggests that the IL-10 G-1082A gene promoter polymorphism is not a major genetic regulator in the etiology of preeclampsia.
Keywords: ARMS PCR; Cytokines; Interleukin-10; Polymorphism; Preeclampsia